Development of carbon nanotube organic thermoelectric materials using cyclodextrin polymer: control of semiconductor characteristics by the solvent effect. (17th January 2020) - Hata, Shinichi; Mihara, Taiki; Shiraishi, Misaki; Yamaguchi, Yuya; Du, Yukou; Shiraishi, Yukihide; Toshima, Naoki
Abstract: The π -type organic thermoelectric conversion modules composed of p-type and n-type materials that convert low-temperature waste heat into electric energy have the potential to significantly increase energy efficiency. However, p-type and n-type materials are difficult to prepare by similar methods since they have opposite carriers. In this study, we achieved γ -cyclodextrin polymer-carbon nanotube (P γ CyD-CNT) composite thermoelectric film that can control the carrier by the solvent effect. When the preparation solvent switched from water to N -methylpyrrolidone (NMP), the carriers of the film were converted from holes to electrons, and their power factor values at 345 K were 221.0 and 246.6 μ W m −1 K −2 . Moreover, P γ CyD-CNTs film prepared in NMP retained n-type characteristics for half a year under the ambient atmosphere. Interestingly, the residual NMP contained in the film acts as a dopant agent for CNTs, and the chemical interaction of γ CyD and NMP in the polymer results in sustained n-doping.